A framework to support the design of a regenerative indoor environment - Pistore, Lorenza; Konstantinou, Thaleia; Pasut, Wilmer; Naboni, Emanuele (Frontiers in Built Environment, 2023)
In recent decades, a new generation of "green indoor" spaces has fulfilled the latest regulations and guidelines for a carbon-neutral society. Their targets are reachable through certifications embracing sets of measures and the adverse effects on occupants. Notwithstanding this, it has constituted a significant step forward in building design. However, the challenges given by climate change and the ecological crises lead to the need for new disruptive approaches to indoor design and function, enhancing human health and adopting regenerative design" at the forefront of buildings' conception. Besides the positive energy-performance attributes, the creation of a Regenerative Indoor Environment (RIE) utilizes appropriate construction technologies and systems, to reinforce human health, and enhance users' experience. This regenerative paradigm shift foresees putting ecosystems at the centre and the users' psycho-physiological wellbeing, thus magnifying their collaboration. Despite regenerative design gaining some attention, a framework towards its implementation promoting the actual performances of the indoor environment is still missing, and designers do navigate among guidelines with no apparent performance indicators to be achieved, technologies to be implemented, or methodologies for post-occupancy evaluations. These three levels, constituting a stepwise methodology, are addressed by the authors within the sections of this paper, and validated as an example of the office buildings' typology. i) What characterizes a Regenerative Indoor Environment? ii) What technical solutions underpin the realization of a Regenerative Indoor Environment? iii) What methods or standards are crucial for its evaluation? With these premises, the